GEOARCHAEOLOGY OF THE EARLY MEDIEVAL STRONGHOLD SURROUNDINGS IN GRZYBOWO NEAR WRZEŚNIA, GREATER POLAND - Marcinkowski, Michał; Szczepaniak, Małgorzata (Quaestiones Geographicae, 2019)
The stronghold in Grzybowo (Rabieżyce village) near Września is a remnant of medieval ring-fort. It is investigated to a considerably lower degree than similar objects from Greater Poland. The analysis of archival data shows that the stronghold is located on the edge of the flood plain of the Struga River formed by Holocene sediments, cutting into the moraine plateau. Analysis of sediments in the stronghold vicinity revealed interlayers of organic matter and sandy deposits rich in calcium carbonate with variable grain size composition, particularly west of the stronghold (i.e. in the valley floor). Moreover, radiocarbon data set showed a considerably older than Holocene age of the sediment. The analysis of the course of the contemporary river channel also allowed for stating hypotheses regarding a potentially different course of the former Struga River channel and its changes during the development of the stronghold. These assumptions were based on the analysis of the archaeological archival data, where field drawings suggest the existence of such a channel in the territory of the stronghold.